Parque Nacional de Jericoacoara: zoneamento para gestão e uso público - Arruda, Maíra Gomes Cartaxo de (2007)
Jericoacoara is known as one of the prettiest beaches in the world, reason for a great tourist attraction in the northeastern coastal. In 2002 the area around Jericoacoara’s Village became the National Park of Jericoacoara, conservation for integral protection unit of 8.416ha, where only the indirect use is allow. The morphology of Jericoacoara is less frequent in the coast, it is a promontory supported by a crystalline substratum of a rocky outcrop from the Precambrian Age called popularly “serrate”. But it is the great charge dunes that point out and dislocate in E - W direction - for the accomplishment of by-pass, that is, the transport of sediments, through the promontory. The main negative environment impact in the Park is the disordered ways, for where they cross the 4x4 vehicles. There are three passages to access the Village; for the beach east, the Track of the Preá; for the south part, the Track of the Lagoa Grande; and for the west, the Track of the Mangue Seco. The indiscriminate transit of vehicles, without a determined fixed route, cause many environment damages, mainly to the fragmentation process in the lagoons that are placed between dunes, intervening in the habitat of the local fauna and modifying the fixing vegetation, it increases the eolic sand´s volume transport process (main morphologic agent). With the accomplishment of the integrated environment diagnosis, a database was elaborated and it should be used to elaborate a managing plan. Actions of tourism order, visitation’s tracks, the characteristics of limitations and vulnerabilities from the environment systems, proposal of the buffer area, recovery and management of the sectors reached for the disordered and random traffic of vehicles had all been defined. With a delimitation of axis routes with points in the GPS and plotted in satellite images, with intermediate sectors for seasons of the bigger precipitations, the impacted areas can be drastically reduced, helping the management in the National Park of Jericoacoara. To identificate the geoenvironments units was the base to understand the processes, the accomplishment of the diagnosis, which subsidized the definition of the zoning for the management and public use for the unit.The zoning have: the intangible zone with 1,751.4ha being 20.7% of the total park areas; the primitive zone with 4,439.4ha, representing most of the park (52.1%); the zone of extensive use, with 1,444ha and 17% of the total park area; zone of recovery, with 920.6ha and 10% of the total park area, and the zone of special use represented by the axis routes. Each zone has defined characteristics and specific norms.